2006
DOI: 10.1089/neu.2006.23.830
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Is Protective in Spinal Cord Injury in Post- and Pre-Menopausal Rats

Abstract: The neuroprotective effects of 17 beta -estradiol have been shown in models of central nervous system injury, including ischemia, brain injury, and more recently, spinal cord injury (SCI). Recent epidemiological trends suggest that SCIs in elderly women are increasing; however, the effects of menopause on estrogen-mediated neuroprotection are poorly understood. The objective of this study was to evaluate the effects of 17beta-estradiol and reproductive aging on motor function, neuronal death, and white matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 126 publications
7
59
0
1
Order By: Relevance
“…The findings do not exclude additional effects of estrogens or related steroids that might be mediated by ERβ, or nonclassical effects, on astrocytes or other CNS cell types, including neurons (8,20,21). Sexual dimorphism is increasingly recognized in CNS molecular mechanisms (23), and circulating levels of endogenous or administered estrogens influence disease severity in a wide variety of CNS disorders, including autoimmune inflammation (4), traumatic injury (24,25), stroke (3), and neurodegenerative disease (1,3,26), all of which have postulated inflammatory involvement. Our findings show that astrocytes are the principal cells required for mediating the neuroprotective effects of ERα signaling in an autoimmune CNS inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…The findings do not exclude additional effects of estrogens or related steroids that might be mediated by ERβ, or nonclassical effects, on astrocytes or other CNS cell types, including neurons (8,20,21). Sexual dimorphism is increasingly recognized in CNS molecular mechanisms (23), and circulating levels of endogenous or administered estrogens influence disease severity in a wide variety of CNS disorders, including autoimmune inflammation (4), traumatic injury (24,25), stroke (3), and neurodegenerative disease (1,3,26), all of which have postulated inflammatory involvement. Our findings show that astrocytes are the principal cells required for mediating the neuroprotective effects of ERα signaling in an autoimmune CNS inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that 17b-estradiol administration reduces secondary injury and promotes functional recovery after SCI, but the dosing and administration timing vary substantially between studies. For example, we have previously shown that pretreatment with a sustained physiological dose of 17b-estradiol to adult or aged female rats decreased apoptosis in the gray matter, increased white-matter sparing, and increased recovery of hindlimb locomotion (Chaovipoch et al, 2006). Similarly, Webb and colleagues (2006) found that pre-injury administration with a sustained physiological dose of 17b-estradiol reduced the severity of autonomic dysreflexia following SCI in male mice.…”
mentioning
confidence: 87%
“…Crush injury to the mid-thoracic spinal cord was performed, with slight modification, as previously described (Chaovipoch et al, 2006). Briefly, rats were anesthetized by an intraperitoneal (i.p.)…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Following spinal hemisection, Gwak et al (2004) reported that 12-month old rats demonstrated greater locomotor deficits (BBB, paw withdrawal latency) than 40 and 60-day old rats. Chaovipoch et al (2006) inferred a protracted time course of cell death following complete crush atT8-9 in 12-month compared to 2-month old rats, based on the number of TUNEL positive (apoptotic) cells in the gray matter. Finally, Siegenthaler et al (2008a;2008b) reported that following thoracic spinal cord contusion injuries, 12 (aged) and 30-month old (geriatric) rats showed less spontaneous recovery of walking, slower bladder function recovery, greater demyelination and less remyelination than 3-month old rats.…”
Section: Introductionmentioning
confidence: 99%